(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Children with special needs face various barriers to learning and development. Play therapy is one way to help them develop optimally and perform their social functions effectively. Play therapy is a therapeutic activity that utilizes toys and games to facilitate children’s expression of various emotions, including happiness, sadness, anger, resentment, depression, and others. The goal of this activity is to help children with special needs increase their concentration and develop creativity and motor skills. The method of implementing play therapy in children with special needs involves several approaches and strategies tailored to individual needs, including group play therapy, structured play therapy, visual techniques, and motor training through penguin gymnastics. Activities are divided into several sessions. During the first session, we divided the children into three groups using a division system that involved coloring paper pictures of three different types of animals. Once the coloring session concluded, the children transitioned to the next activity, which involved arranging pyramids using plastic cups to enhance their concentration, despite their frequent distractions in practice. The last activity is for children to do motor exercises with penguin gymnastics. Children with special needs follow each session according to the therapist’s direction. We hope that the child’s parents will participate regularly and schedule the activities to ensure the program’s sustainability.